Correlation of primary students’ physical activity and progress in regulatory functions - Shatskaya, A.N.; Veraksa, A.N.; Fominykh, A.Y. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze correlations between regulatory functions and physical activity in primary school groups. Methods and structure of the study. We sampled for the study the 8 year-old 2-grade students (n=103, 47 boys and 56 girls) at Moscow schools and split them up into unsporting Group 1 (n=49) and sporting Group 2 (n=54) of individuals trained at least twice a week for 45+min in 1+ sport groups on an off-class basis for at least one year. The sample was tested on an individual basis, with the test data processed by SPSS 21.0 software written in R-language (version 4.0.3). We used NEPSY-II Neuropsychological Test System (designed to test mental functions in the 3-16-year-olds) to rate the self-regulation elements in the sample. Visual operational memory was rated by a Design Memory subtest; restraining control by an Inhibition subtest run in two series with different triggers/ stimuli; cognitive flexibility by a Sorting Animals subtest using cards with animals; and the short-term auditory memory was rated by the A.R. Luria’s Ten Words test. Results and conclusion. Our tests and and analyses rated the habitually sporting children meaningfully higher on the self-regulation and short-term auditory memory scales than their unsporting peers, with the highest progress and intergroup differences in the cognitive flexibility tests. This finding gives us the reasons to recommend reasonably high physical activity among the most efficient cognitive progress facilitation methods.